2019
DOI: 10.1063/1.5095583
|View full text |Cite
|
Sign up to set email alerts
|

Surface chemistry of 2,3-dibromosubstituted norbornadiene/quadricyclane as molecular solar thermal energy storage system on Ni(111)

Abstract: Dwindling fossil fuels force humanity to search for new energy production routes. Besides energy generation, its storage is a crucial aspect. One promising approach is to store energy from the sun chemically in strained organic molecules, so-called molecular solar thermal (MOST) systems, which can release the stored energy catalytically. A prototypical MOST system is norbornadiene/quadricyclane (NBD/QC) whose energy release and surface chemistry need to be understood. Besides important key parameters such as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 68 publications
0
33
0
Order By: Relevance
“…Fundamental understanding of these complex processes can be obtained by surface science studies in ultra-high vacuum (UHV). 107 In recent years, this approach was used to study energy release from the NBD/QC couple on Pt(111) 108,109 and Ni (111). 110,111 It was found that Pt( 111) is significantly more active for triggering the energy release than Ni (111).…”
Section: Controlling Energy Releasementioning
confidence: 99%
See 2 more Smart Citations
“…Fundamental understanding of these complex processes can be obtained by surface science studies in ultra-high vacuum (UHV). 107 In recent years, this approach was used to study energy release from the NBD/QC couple on Pt(111) 108,109 and Ni (111). 110,111 It was found that Pt( 111) is significantly more active for triggering the energy release than Ni (111).…”
Section: Controlling Energy Releasementioning
confidence: 99%
“…107 In recent years, this approach was used to study energy release from the NBD/QC couple on Pt(111) 108,109 and Ni (111). 110,111 It was found that Pt( 111) is significantly more active for triggering the energy release than Ni (111). 108,110 On clean Pt (111), a monolayer of QC is immediately back-converted to NBD even at cryogenic temperatures (125 K).…”
Section: Controlling Energy Releasementioning
confidence: 99%
See 1 more Smart Citation
“…Interconversions between NBD and QC, and their derivatives are very important, since a promising approach to energy storage from the sun, lies in the use of strained organic molecules. [4][5][6][7] This justifies a brief summary. These so-called molecular solar thermal (MOST) binary systems, absorb solar energy via the alkene form (here NBD) leading to the strained form (here QC); the stored energy can then be released from the latter catalytically, regenerating the NBD.…”
Section: Introductionmentioning
confidence: 75%
“…[1] Practical interest in norbornadiene thermochemistry is based on the potential use of the norbornadiene-quadricyclane isomerization as a solar energy storage system. [2][3][4][5] Although the enthalpies of formation (Δ f H ) of these compounds have been measured repeatedly (see References [1,[6][7][8][9] and references therein), there is still disagreement in their values. Only the experimental value of Δ f H (g) for norbornane recommended by…”
mentioning
confidence: 99%